2009
DOI: 10.1158/0008-5472.can-08-3199
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Analysis Identified Epidermal Growth Factor Receptor Activation as the Most Common Genetic Event in Oral Squamous Cell Carcinoma

Abstract: A 250K single-nucleotide polymorphism array was used to study subchromosomal alterations in oral squamous cell carcinoma (OSCC). The most frequent amplification was found at 7p11.2 in 9 of 29 (31%) oral cancer patients. Minimal genomic mapping verified a unique amplicon spanning from 54.6 to 55.3 Mb on chromosome 7, which contains SEC61G and epidermal growth factor receptor (EGFR). Results from fluorescence in situ hybridization, transcriptome, and immunohistochemistry analyses indicated that the expression le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 47 publications
8
113
1
1
Order By: Relevance
“…For example, using a genome-wide analysis of DNA copy number changes, we have previously demonstrated that amplification at the ch7p11.2 locus, which harbors epidermal growth factor receptor (EGFR), was the most common DNA copy number alteration in OSCC tissues. 19 Up-regulation of other known oncogenes, such as CCND1 and FGFR genes, was also frequently found in OSCC. 19,22,23 In this study, we demonstrate that a chromatin remodeling factor, RSF-1, may be involved in tumor progression, and may confer disease aggressiveness in OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, using a genome-wide analysis of DNA copy number changes, we have previously demonstrated that amplification at the ch7p11.2 locus, which harbors epidermal growth factor receptor (EGFR), was the most common DNA copy number alteration in OSCC tissues. 19 Up-regulation of other known oncogenes, such as CCND1 and FGFR genes, was also frequently found in OSCC. 19,22,23 In this study, we demonstrate that a chromatin remodeling factor, RSF-1, may be involved in tumor progression, and may confer disease aggressiveness in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…19 Up-regulation of other known oncogenes, such as CCND1 and FGFR genes, was also frequently found in OSCC. 19,22,23 In this study, we demonstrate that a chromatin remodeling factor, RSF-1, may be involved in tumor progression, and may confer disease aggressiveness in OSCC. Moreover, RSF-1 knockdown experiments showed that RSF-1 expression was essential for tumor cell growth and survival in RSF-1-overexpressing OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, epidermal growth factor receptor (EGFR) has been identified to be amplified in 31% of OSCC patients and correlates with poor clinical outcome. Targeting of EGFR with either a monoclonal antibody against EGFR or a small-molecule EGFR tyrosine kinase inhibitor has been successfully utilized for therapeutic purposes (16,17). Currently, it is believed that personalized treatment is the major cancer therapy strategy in the future.…”
Section: Introductionmentioning
confidence: 99%